PENGARUH KUALITAS PRODUK DAN CITRA MEREK TERHADAP KEPUASAN PELANGGAN HELM MEREK KYT DI KECAMATAN BINTARA KOTA BEKASI - Berlian Rahmatulah; Dr. Ismail Razak, M.Si. (Jurnal Manajemen Bisnis Krisnadwipayana, 2019)
The aim of this study was to analize the influence of product quality and brand image on the satisfaction of customers. Primary data was obtained from customers of helm KYT in Kecamatan Bintara Bekasi City. In this study is used purposive sampling method. Data analysis technique used in this research is simple linear regression and multiple linear regression. The results of this study indicated that product quality and brand image positively and significant influenced the satisfaction of customers.